Impact of COVID-19 on academic activities of final year nursing students: a Zambian reflection - Mwila, Kennedy; Kalolo, Florence; Mudenda, Steward; Hikaambo, Christabel Nangandu (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The novel coronavirus disease 2019 (COVID-19) has had many impacts on the education sector. The pandemic has had negative impacts on the academic activities of nursing students globally. Therefore, we assessed the impact of the COVID-19 on final year nursing students’ academic activities in Lusaka and Mufulira districts of Zambia. Methods: This was a cross-sectional study that employed quantitative methods using a structured questionnaire among 196 final year nursing students from 1August 2020 to 30 September 2020. Data were analysed using the statistical package for social sciences (SPSS) version 21. Results: A female predominance (67.9%) and a response rate of 86% were obtained. Many students strongly agreed (32.7%) and agreed (20.4%) that they did not complete their course work resulting in some concepts being poorly taught, 86.1% strongly agreed that they had delayed final examinations, and 51.5% strongly agreed that they did not do their clinical attachments. Students strongly disagreed (40.3%) that the e-library and wireless facilities in their school were well-stocked. Hence, this resulted in some students (40.3%) missing class lessons and assessments. Conclusions:The COVID-19 epidemic has negatively affected the academic activities of nursing students in Zambia. Ministries responsible for education must put in place measures that will mitigate the impact of COVID-19 on the education sector. Schools must adapt to the changes in the way of conducting learning and assessment sessions. Finally, schools must improve on their e-library and wireless facilities to effectively support online learning.